Prevalence, virulence profiles and antibiotic susceptibility patterns of Shiga toxin producing Escherichia coli O157:H7 among children 6–59 months in Longido, Arusha-Tanzania - Martin Michael Martin; Haikael David Martin; Beatus Modesty Lyimo (PLoS ONE, 2026)
Shiga toxin producing Escherichia coli (STEC) is a zoonotic pathogen associated with diarhoeal disease and severe complications in children, yet its epidemiology in pastoral settings of Tanzania remains insufficiently characterized. This study determined the prevalence, virulence gene profiles and antibiotic susceptibility patterns of STEC among children aged 6‍-59 months with diarhoea in Longido District, northern Tanzania. A hospital based cross-sectional‍ study was conducted between July and August 2025, enrolling 150 participants from four health facilities. Stool samples were collected and analyzed using culture, serological conformation and multiplex polymerase chain reaction targeting five genes; rfbE , stx1 , stx2 , eae A and hly A . STEC was operationally defined by detection of stx1 and/or stx2 . Antibiotic susceptibility was assessed using the Kirby-Bauer disk diffusion method. The prevalence of STEC was‍ 13.3% (20/‍150). All stx2 positive isolates co-occurred with stx1 . Virulence genes showed a heterogeneous but significantly clustered distribution, with rfbE (20.0%) and stx1 (13.3%) predominating. Significant co-occurrence was observed‍ between stx1 and eae and between stx1 and hlyA (p < .001). Animal contact, raw milk consumption and use of untreated water were significantly associated with STEC infection. Firth penalized logistic regression confirmed these exposures as independent predictors. Antibiotic susceptibility profiles were uniform, with complete susceptibility to ciprofloxacin,‍ gentamicin, cefotaxime and ceftazidime while ampicillin and trimethoprim showed complete resistance. These findings indicate that STEC transmission in pastoral communities is strongly driven by zoonotic and environmental exposures, characterized by clustered virulence determinants and consistent antibiotic profiles. Limitations include the cross-sectional design and short sampling period, which may not capture seasonal variation. Strengthened surveillance and integrated One Health interventions are needed to reduce disease burden.